Middle Cambrian (Miaolingian) acritarchs from the Flagg Cove Formation, Grand Manan Island, New Brunswick, Canada: Stratigraphic implications and possible correlations - Johnson, Susan C.; White, Chris E.; Palacios, Teodoro; Jensen, Sören; Barr, Sandra M. (Atlantic Geoscience)

(untitled) (Atlantic Geoscience Society, 2024)
The upper Ediacaran to lower Cambrian Castalia Group as originally defined comprises a basal sequence of clastic marine sedimentary rocks assigned to the Great Duck Island and Flagg Cove formations and an upper sequence of mainly mafic volcanic and volcaniclastic rocks of the Ross Island, North Head, Priest Cove, and Long Pond Bay formations. A few previously reported specimens of the long-ranging trace fossil Planolites in the Flagg Cove Formation were not inconsistent with the U–Pb age of 539.0 ± 3.3 Ma age for the Priest Cove Formation or the interpreted intrusive relationship between the Flagg Cove Formation and 535 ± 2 Ma Stanley Brook Granite.During a recent visit, abundant morphologically simple trace fossils, including Planolites, were recognized in strata south of Stanley Beach in Flagg Cove, together with vertically or obliquely oriented trace fossils more than 10 mm in diameter, and probable Teichichnus. The age of this association of trace fossils is post earliest Fortunian. More significantly, grey silty shale interbedded with the sandstone that contains the traces yielded organic-walled microfossils. The microfossils include the acritarch Micrhystridium spp of a type also found in the King Square Formation in the Saint John area. The microfossils suggest a Miaolingian (middle Cambrian) age for the Flagg Cove Formation, requiring that its relationship with the Stanley Brook Granite and Castalia Group needs to be re-examined. it also raises the possibility of correlation with middle Cambrian clastic sedimentary sequences exposed on mainland southern New Brunswick and elsewhere in the region.